E-Selectin, and markers of HIV disease severity, inflammation and coagulation in treatment- naïve individuals living with HIV - Hoffman, Madelein (Stellenbosch : Stellenbosch University, 2015)
ENGLISH SUMMARY: Background: E-selectin is an adhesion molecule that is expressed on the surface of activated endothelial cells. During inflammation the endothelial cells are activated, trafficking cells of the immune system through the endothelial wall to the point of inflammation. Human Immunodeficiency Virus (HIV) infection causes continuous and long term activation of the immune system and has an increased incidence of cardiovascular disease. Selectins play an important role in atherosclerotic plaque formation as continuous activation leads to plaque formation and eventual plaque rupture with subsequent thrombosis and the initiation of a cardiac event. The aim of this study was to determine the levels of E-selectin in an HIV infected and control population and to correlate these levels with markers of HIV disease severity, inflammation and coagulation in anti-retroviral treatment (ART)-naïve HIV infected individuals. Methods: E-selectin levels were determined using ELISA in 180 participants from an HIV prevention and testing clinic in Crossroads, Cape Town. There were 114 HIV infected cases and 66 HIV negative controls. These levels were compared with each other and correlated to various other markers associated with HIV disease severity (viral load and CD4+count), inflammation (white cell count (WCC), high sensitivity C-reactive protein (hsCRP), %CD38/8, albumin and IgG) and coagulation (fibrinogen and D-dimer). Results: A total of 75% of the females tested positive for HIV compared to 37% of the males. Statistics comparing HIV status with WCC, CD4+count, %CD38/8, albumin, IgG, hsCRP and D-dimer found significant differences (p<0.01) between the two groups. No differences in E-selectin (p=0.84) and fibrinogen (p=0.65) levels were found between the cases and the controls. When E-selectin was compared with all the analytes tested, significant correlations were found with age (p=0.02) and gender (p=0.01). Albumin (p=0.05) showed a significant correlation with E-selectin in the control group. The correlation with the WCC (p=0.07) in the HIV infected group neared significance. Conclusion: No significant difference in E-selectin levels was found between the HIV positive and negative control group and no correlations were found with Eselectin and the markers of disease severity, inflammation and coagulation. Thus we found E-selectin to be a poor marker of inflammation in this setting. As age and gender are established markers of CVD and males have higher E-selectin levels than females, the lack of significance may be due to our sample population’s young age (mean 31 years) or the fact that 70% of the cohort was female. Thus significant endothelial damage may not yet have taken place to increase E-selectin levels. In addition, this HIV group was predominantly in the chronic stage of infection, therefore the increase in E-selectin levels may have occurred earlier during the acute infection.